THE IMPACT OF INSTAGRAM SOCIAL MEDIA ADVERTISING AND IN-STORE AMBIENCE ON CUSTOMER SATISFACTION AT JANGKAR TOMOHON - Togas, Tesalonika; Saerang, David P.E.; Tielung, Maria V.J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The, inconsistencies between online promotions and the actual in-store atmosphere have created varying levels of customer satisfaction. This study aims to analyze the impact of Instagram social media advertising and in-store ambience on customer satisfaction at Jangkar Tomohon. This research applies a quantitative approach using multiple linear regression to determine the partial and simultaneous effects of both variables. Data were collected through questionnaires distributed to 100 respondents who have visited Jangkar Tomohon and follow its Instagram account. The results show that both Instagram social media advertising and in-store ambience have a significant effect, either partially or simultaneously, on customer satisfaction. These findings emphasize the importance of aligning digital advertising strategies with the actual physical experience to enhance customer satisfaction and strengthen café competitiveness in Tomohon.   Keywords: Social Media Advertising, In-Store Ambience, Customer Satisfaction